An assessment of diabetes care in Palestinian refugee camps in Syria - Alabed, Samer (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Palestinian refugees have been a displaced group of people since 1948, many of whom are living in refugee camps in the Middle East. They are entitled to free health care from the United Nations Relief and Work Agency (UNRWA). They show a higher prevalence of diabetes than the population in their host countries in the Middle East. This study examined the realities of care for diabetic patients in UNRWA health clinics in Damascus, Syria. The aim was three-fold: To investigate the level of diabetes care, to probe patients’ level of general understanding of their disease and its management, and to search for areas of potential improvement. METHODS: Data on patient education and care was gathered over a 1 month period from August 4, 2008 to September 4, 2008 using questionnaires and direct observation of the workflow at the clinics. Clinic-led care was observed by the study team using checklists during patient visits. All of the clinic staff and sampled patients were interviewed. The main areas of care assessed were: Patient follow-up; examination of eyes and feet; availability of medications; and patient education. A total of 154 people with diabetes were sampled from three refugee camps situated around Damascus. RESULTS: A total of 154 patients, three doctors and seven nurses composed the sample of the study. Foot examinations were almost always neglected by health staff and eye examinations were not offered by the UNRWA clinics. Interviews with patients showed that: 67% (95% confidence intervals [CI]: 0.59-0.70) had to buy their medication at their own expense at least once due to medication shortage in the UNRWA clinics, 48% (95% CI: 0.40-0.55) displayed poor knowledge regarding the cause and exacerbating factors of diabetes, 65% (95% CI: 0.56-0.72) had not heard of insulin, and 43% (95% CI: 0.35-0.51) did not know for how long they needed to take their medications.